Platinum-based drug-induced depletion of amino acids in the kidneys and liver - Mitrevska, Katerina; Cernei, Natalia; Michalkova, Hana; Rodrigo, Migue Angel Merlos; Sivak, Ladislav; Heger, Zbynek; Zitka, Ondrej; Kopel, Pavel; Adam, Vojtech; Milosavljevic, Vedran (Frontiers in Oncology, 2022)
Cisplatin (cis-diamminedichloroplatinum II; CDDP) is a widely used cytostatic agent; however, it tends to promote kidney and liver disease, which are a major signs of drug-induced toxicity. Platinum compounds are often presented as alternative therapeutics and subsequently easily dispersed in the environment as contaminants. Due to the major roles of the liver and kidneys in removing toxic materials from the human body, we performed a comparative study of the amino acid profiles in chicken liver and kidneys before and after the application of CDDP and platinum nanoparticles (PtNPs-10 and PtNPs-40). The treatment of the liver with the selected drugs affected different amino acids; however, Leu and Arg were decreased after all treatments. The treatment of the kidneys with CDDP mostly affected Val; PtNPs-10 decreased Val, Ile and Thr; and PtNPs-40 affected only Pro. In addition, we tested the same drugs on two healthy cell lines, HaCaT and HEK-293, and ultimately explored the amino acid profiles in relation to the tricarboxylic acid cycle (TCA) and methionine cycle, which revealed that in both cell lines, there was a general increase in amino acid concentrations associated with changes in the concentrations of the metabolites of these cycles.